PETA POTENSI DALAM MENCIPTAKAN KEMANDIRIAN EKONOMI DESA - Edriana Pangestuti; Inggang Perwangsa Nuralam; Muhammad Tanzil Furqon; Hanifa Maulani Ramadhan (JOURNAL OF APPLIED BUSINESS ADMINISTRATION, 2018)
Law Number 6 of 2014 concerning village stipulation is meant in developing village potential and assets in order to develop together, and advance the economy of rural communities. This is an opportunity for every village to develop every potential they have. It needs to be highlighted that Tawang Argo Village, Karangploso Subdistrict, Malang Regency is experiencing maximixing the facilities available in Universitas Brawijaya Educational Forest (Hutan UB). This study aims to map the potential that is capable and developed in Tawang Argo Village. This study uses a qualitative approach and strengthens SWOT, EFAS, and IFAS analysis. Several factors found from the results of this study include: 1) lack of product innovation; 2) land conditions in the highlands that are not supported by economic commodities; 3) lack of creativity in the community; and 4) small market opportunities. Imaging which shows that Tawang Village is very appropriate to build House of Mushrooms as a potential solution that exists. In cultivating mushroom kumbung not by the condition of the residents' land, having their own planting media with temperature regulation can also be planted on limited land. The results of mushroom kumbung can be sold in the form of raw materials and processed to add value and be developed into a product that is competitive and builds the independence of the village economy.